7x-12x-5=-43+15

Simple and best practice solution for 7x-12x-5=-43+15 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7x-12x-5=-43+15 equation:


Simplifying
7x + -12x + -5 = -43 + 15

Reorder the terms:
-5 + 7x + -12x = -43 + 15

Combine like terms: 7x + -12x = -5x
-5 + -5x = -43 + 15

Combine like terms: -43 + 15 = -28
-5 + -5x = -28

Solving
-5 + -5x = -28

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5' to each side of the equation.
-5 + 5 + -5x = -28 + 5

Combine like terms: -5 + 5 = 0
0 + -5x = -28 + 5
-5x = -28 + 5

Combine like terms: -28 + 5 = -23
-5x = -23

Divide each side by '-5'.
x = 4.6

Simplifying
x = 4.6

See similar equations:

| 4(a-6)+10=2(a-5) | | 4xsquared+3=0 | | 10-1/4(8x-12)1/2(2x-4) | | 0.9x-0.7(3-x)=5.1 | | .25(98)+.75(94)= | | 15x+20y=24x+46y | | 4w^3-5w^2-8w+10=0 | | g(x)=x^3-6x^2+16 | | 1-4x/5=9 | | 3-3(4w-3)+w= | | 2x+17=75 | | 3g+20=20g+2 | | 2g+20=20g+2 | | -a=-P+3b+4c | | 3h+3=7h-17 | | 5d+6=4d+12 | | 9/4÷3/8= | | 13c/4d/2c | | 9/4÷3/8 | | 3b-7=5b-23 | | 7x+1-3(x+1)=9x+2 | | 18v^6w^9-12vw^6x^2=0 | | 3(6+2x)=3x+6 | | 7-3(x-2)=7-x(4-4x) | | 57/95=18/x | | (8z-6)=90 | | 2n+3=113 | | 4x+6x+7y+9y= | | 4x+19+3x+2=90 | | 4x+19+3x+2=180 | | 0.3/Q | | -4+12y+9=16+16y-39 |

Equations solver categories